Psychological Well-Being And Work Motivation Amongst Medical Professionals - Rehman, Ghazala; Malik , Najma Iqbal; Taj , Rizwan (Journal of Pakistan Psychiatric Society, 2006)
Objective: The study examines the relationship of psychological well-being and work motivation in a sample of Pakistani medical professionals. Design: Cross sectional comparative study. Place and duration of the study: The study was conducted in private (Alshifa International Hospital, Islamabad, and Islamabad Private Hospital) and public sector hospitals (Pakistan Institute of medical Sciences and Rawalpindi General Hospital) in the twin-cities of Islamabad and Rawalpindi, Pakistan dur ing 2002. Subjects and Methods: A sample of 120 medical professionals belonging to the private and public sector hospitals (n=60 in each) participated in the study. They were selected on the basis of purposive convenient sampling technique. The data was collected with the help of Psychological Well-Being Scale (Wb) and Work Preference Inventory (WPI) and a separately devised demographic sheet containing infor mation about age, experience and private and public sector affiliation. Results: The age range of the sample was between 30-60 years (M=42.97, SD=7.96). The range of experience in service was 1-42 years (M=16.28, SD=8.43). Scores of psychological well being had a significant inverse co-relation with extrinsic motivation (r=-0.26, p < .01). Public and private sector doctors showed a highly significant difference in their motivational orientation (p < .01). The relation of age with scores of well being and motivation showed a significant difference, (t=3.9, p<.001) and (t=2.41, p<0.05) between those aged 53 and above and those 41 years of age or less respectively. Conclusion: Compared to the private sector, the environment of public sector is perceived to be more challenging. Similarly, older medical professionals seem to be having higher psychological well-being and work motivation, compared to the younger medical professionals. However, these findings suggest the need for further exploration of some interrelated variables, which might give us insight for future policy implementation, suggesting ways for further improvement in the psychological facets of the work environment of this dynamic group of professionals. Key words: Psychological well-being, Work Motivation, Intrinsic Motivation, Extrinsic Motivation, Multiple Occupational Roles (MOR).